Genetic Control Diversity Drives Differences Between Cadmium Distribution and Tolerance in Rice - Chen, Yi-Bo; Chen, Yu-Chao; Zhu, Yu-Xing; Li, Sai; Deng, Hua-bing; Wang, Jiu-Rong; Tang, Wen-Bang; Sun, Liang (Frontiers in Plant Science, 2021)
Rice, as a staple crop for nearly half the planet’s population, tends to absorb and accumulate excessive cadmium (Cd) when grown in Cd-contaminated fields. Low levels of Cd can degrade the quality of rice grain, while high levels can inhibit the growth of rice plants. There is genotypic diversity in Cd distribution and Cd tolerance in different rice varieties, but their underlying genetic mechanisms are far from elucidated, which hinders the genetic improvements in rice. In this study, a joint study of phenotypic investigation with quantitative trait loci (QTL) analyses of genetic patterns for Cd distribution and Cd tolerance was implemented using a bi-parent population derived from japonica and indica rice varieties. We identified multiple QTLs for each trait, and revealed that additive effects from various loci drive the inheritance of Cd distribution, while epistatic effects between various loci contribute to differences in Cd tolerance. One pleiotropic locus, qCddis8, was found to affect Cd distribution from roots to and shoots, and from sheaths and leaves. The results expand our understanding of the diversity of genetic control over Cd distribution and Cd tolerance in rice. The findings could prove useful for breeding low-grain-Cd rice varieties.